RNA-Binding Protein HuR Suppresses Inflammation and Promotes Extracellular Matrix Homeostasis via NKRF in Intervertebral Disc Degeneration - Shao, Zhenxuan; Tu, Zhuolong; Shi, Yifeng; Li, Sunlong; Wu, Aimin; Wu, Yaosen; Tian, Naifeng; Sun, Liaojun; Pan, Zongyou; Chen, Linwei; Gao, Weiyang; Zhou, Yifei; et al. (Frontiers in Cell and Developmental Biology, 2020)
Intervertebral disc degeneration (IVDD) has been reported to to be a major cause of low back pain. Studies have demonstrated that IVDD may be dysregulated at transcriptional level; however, whether post-transcriptional regulation is involved is still unknown. The current study aimed to illustrate the role of HuR, an RNA binding protein involved in post-transcriptional regulation, in IVDD. The results showed that the expression of HuR was decreased in degenerative nucleus pulposus (NP) tissues as well as in TNF-α treated NP cells. Down-regulation of HuR may lead to increased inflammation and extracellular matrix (ECM) degeneration in TNF-α treated NP cells; however these effects were not reversed in HuR over-expressed NP cells. Inhibition of NF-κB signaling pathway attenuates inflammation and ECM degeneration in HuR deficient NP cells. Mechanism study showed that HuR prompted NKRF mRNA stability via binding to its AU-rich elements, upregulation of NKRF suppressed inflammation and ECM degeneration in HuR deficient NP cells. Furthermore, we found that NKRF, but not HuR, overexpression ameliorated the process of IVDD in rats in vivo. In conclusion, HuR suppressed inflammation and ECM degeneration in NP cells via stabilizing NKRF and inhibiting NF-κB signaling pathway; NKRF, but not HuR, may serve as a potential therapeutic target for IVDD.